How Nonsectarian is ‘Nonsectarian’?: Jorge Ferrer's Pluralist Alternative to Tibetan Buddhist Inclusivism - Duckworth, Douglas (Sophia, 2014)
This paper queries the logic of the structure of hierarchical philosophical systems. Following the Indian tradition of siddhānta, Tibetan Buddhist traditions articulate a hierarchy of philosophical views. The ‘Middle Way’ philosophy or Madhyamaka—the view that holds that the ultimate truth is emptiness—is, in general, held to be the highest view in the systematic depictions of philosophies in Tibet, and is contrasted with realist schools of thought, Buddhist and non-Buddhist. But why should an antirealist or nominalist position be said to be ‘better’ than a realist position? What is the criterion for this claim and is it, or can it, be more than a criterion that is tradition-specific for only Tibetan Buddhists? In this paper, I will look at the criteria to evaluate Buddhist philosophical traditions, particularly as articulated in what came to be referred as the ‘nonsectarian’ (ris med) tradition. I draw from the recent work of Jorge Ferrer to query the assumptions of the hierarchical structures of ‘nonsectarian’ traditions and attempt to articulate an evaluative criteria for a nonsectarian stance that are not based solely on metaphysical or tradition-specific claims.